(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
In Malaysia, studies sought to evaluate the health-related quality of life (HRQoL) among patients undergoing anticogaultaion therapy are still recent and scarce as there is no specific tool available. This cross sectional descriptive study was undertaken with a representative cohort of atrial fibrillation patients undergoing anticoagulation therapy. Using prevalence based sampling techniques, a total of 339 patients were recruited from the Anticoagulation Clinics at two public hospitals in Penang, Malaysia. A bilingual specific instrument; Duke Anticoagulation Satisfaction Scale (DASS) and a generic instrument; the European Quality of Life scale (EQ-5D-3L) were used for data collection. The mean (SD) age of the patients was 60.4±14.5 years, with 204 (60.2%) males dominating the entire study. The majority of patients were from lower socioeconomic level and one third of subjects had a secondary level of education. DASS instrument presented a good average score of 70.8 (±19.8), while the means±SD of EQ-VAS was 69.3% (± 16.3%) and for the EQ-Index (TTO) was 79.8% (± 26.5%) indicated satisfactory health related quality of life (HRQoL) in our study participants. Their QoL perception is affected positively by age, education level, and occupation and negatively by sex gender and previous hemorrhagic event. The worse evaluations were in mobility and pain domains. Consequently, it was noted that warfarin therapy is not usually associated with a significant decrease in perceived health, unless a bleeding episode has occurred. Results from this study could be useful in clinical practice, particularly in newly detected AF patients, at point where improving HRQoL is still possible.